Desarrollo logístico en los principales puertos para la distribución física internacional en Colombia. (2020)
This document compiles literature on Colombia's logistical development and the variables that impact international physical distribution, so as to improve the country's competitiveness and generate new business opportunities in the international commerce. This improvement should be focused on an adjustment in port logistics, taking into account that ports are an important link in the logistics chain, since they determine the amount of cargo mobilization. Finally, in order to take advantage of the few existing resources in the country, it is necessary to carefully analyze everything related to the transfer of products from their destination to the end user in order to implement a correct Integral Logistic System, which allows the generation of own strategies to be competitive at a global level.